Unité d’analyse en traductologie descriptive. Une contribution à la méthodologie des DTS - Raková, Zuzana (Romanica Silesiana, 2020)
This article aims to specify one method of descriptive analysis, which can be used in the epistemological framework of the Descriptive Translation Studies and the theory of the polysystem. The challenge is essentially to define the unit of analysis in relation to traditional translation methods (borrowing, tracing, literal translation, transposition, modulation, equivalence, adaptation), defined in 1958 by Jean-Paul Vinay and Jean Darbelnet. We aim to associate the comparative stylistics with polysystem theory on the descriptive studies of translation and to propose a method of qualitative and quantitative analysis on corpus of source and target texts. The method could be profitable especially for studies in the field of the history of translation (in the phase of “historical criticism” according to the taxonomy of the discipline formulated by A. Pym).